Overexpression of BMP4 protects retinal ganglion cells in a mouse model of experimental glaucoma. (September 2021) - Liu, Dongmei; Deng, Qinqin; Lei, Xinlan; Lu, Wei; Zhao, Qingqing; Shen, Yin
Abstract: Purpose: Activation of bone morphogenetic protein (BMP) 4 signaling promotes the survival of retinal ganglion cell (RGC) after acute injury. Chordin-like 1 (CHRDL1) is an endogenous BMP antagonist. In this study, we researched whether CHRDL1 was involved in BMP4 signaling and regulation of RGC degeneration in a mouse model of glaucoma. Methods: Magnetic microbeads were intracameral injected to induce experimental glaucoma in a mouse model. A recombinant adeno-associated virus (rAAV) system was designed for overexpression of BMP4 or CHRDL1 in mouse retina. Immunohistochemistry and hematoxylin-eosin (HE) stains were performed to identify changes in retinal morphology. Electroretinogram (ERG) recordings were used to assess changes in visual function. Results: The mRNA expression levels of Bmp4 and its downstream BMPRIa, small mothers against decapentaplegic 1 (Smad1), were significantly upregulated in retinas with glaucoma. RGC survival was significantly enhanced in the beads + AAV-BMP4 group and significantly reduced in the beads + AAV-CHRDL1 group, compared with the beads + AAV-EGFP group. Similar results were observed in retinal explant culture in vitro . Consistent with these findings, the photopic negative response (PhNR)responses in ERG, which indicate RGC function, were restored in mice overexpressing BMP4, whereas a-wave and b-wave responses were not. Activation of CHRLD1 inhibited Smad1/5/8 phosphorylation and exacerbated RGC damage. The expression of Glial fibrillary acidic protein (GFAP) was decreased significantly in beads + AAV-BMP4 group. Conclusions: BMP4 promoted RGC survival and visual function in an experimental glaucoma model. Activation of CHRDL1 exaggerated RGC degeneration by inhibiting the BMP4/Smad1/5/8 pathway. The mechanism of BMP4/Smad1/5/8 pathway may be related to the inhibition of glial cell activation. Our studies suggested that BMP4 and CHRLD1 might serve as therapeutic targets in glaucoma. Highlights: BMP4 was studied in the form of AAV overexpression instead of polypeptide, which achieved long-term stable overexpression of BMP4. BMP4 has a significant protective effect on RGCs in chronic high intraocular pressure glaucoma caused by magnetic microbeads anterior intracameral injection. The neuroprotective effect of BMP4 on RGCs not only existed in morphology, but also in visual function. The neuroprotective effect of BMP4 is via its classic pSmad pathway，which could be inhibited by CHRDL1.